2008
DOI: 10.1089/jpm.2007.0194
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Pediatric Palliative Care Curriculum for Pediatric Residents

Abstract: Pediatric residents who participated in this pilot study felt they learned important skills in pediatric EOL care and enhanced their confidence in their ability to care for dying patients and their families. Interventions like the PPCC may be useful at other institutions and aid in the transition to competency-based training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 26 publications
1
62
0
Order By: Relevance
“…Of the 20 studies that evaluated improvement in knowledge around various palliative care topics, 11 used a written examination, 25,27,34,[38][39][40][41]43,44,48,49 8 asked about self-perceived changes in knowledge 24,29,31,33,35,37,42,47 and 1 used an objective chart review to examine prescribing behavior. 45 All but 2 of these 20 studies 29,44 administered surveys preintervention and postintervention.…”
Section: Knowledgementioning
confidence: 99%
“…Of the 20 studies that evaluated improvement in knowledge around various palliative care topics, 11 used a written examination, 25,27,34,[38][39][40][41]43,44,48,49 8 asked about self-perceived changes in knowledge 24,29,31,33,35,37,42,47 and 1 used an objective chart review to examine prescribing behavior. 45 All but 2 of these 20 studies 29,44 administered surveys preintervention and postintervention.…”
Section: Knowledgementioning
confidence: 99%
“…Pilot studies in pediatrics, using 6 hours of EOL topic discussion, 11 and in adult medicine, with resident exposure to hospice care, 12 showed improvement in residents' knowledge, confidence, and skills, and favorable ratings from participants.…”
Section: Introductionmentioning
confidence: 98%
“…[3][4][5][6][7] Additionally, there have been efforts to measure the impact of the IPPC curriculum 8 and the increased focus on the voices and perspectives of parents of seriously ill children.…”
mentioning
confidence: 99%
“…8 However, no research focuses on the experience of bereaved parents as educators of health care professionals, and efforts to examine health care professionals' perspectives concerning the participation of bereaved parents in palliative care education have been limited. [3][4][5][6][7] The question of negative impact or harm for bereaved parents in research was examined by Hynson and colleagues, and findings suggested that a careful and thoughtful approach can acceptably minimize possible harm and the research experience can even be experienced as a positive one for some parents. 9 The purpose of this qualitative research was to study motivations, expectations, challenges, benefits, and meaningmaking for bereaved parents involved in pediatric palliative care education of health care professionals and to learn about the challenges and possible benefits for the health care professionals.…”
mentioning
confidence: 99%